Validating the accuracy of ESENER-II in assessing psychosocial risks for the case of micro firms in Cyprus. (December 2019) - Stamatogianni, E.; Anyfantis, I.D.; Dimopoulos, C.; Boustras, G.
Highlights: The size of the business and the peculiarities of the Cypriot context impact on the perception and management of psychosocial risks. Difficulties in identifying psychosocial risks are related to the lack of training and awareness within micro-enterprises in Cyprus. The participation of smaller enterprises in our sample comparing to ESENER's has fueled significant differences. Additional research is required for the case of micro SMEs. Abstract: Micro and small enterprises (MSEs) constitute the cornerstone of the economy in each country, especially in the European Union, where they are perceived as main components for economic development, innovation, employment and social integration. Effective management of occupational safety and health (OSH) in MSEs' working environment contributes in sustaining corporate longevity and protects workers' well-being and productivity. This may become essential, especially for economies that are struggling to recover from economic recession. One essential aspect of OSH involves the identification and management of psychosocial risks. EU-OSHA (2010) has launched two significant surveys related to psychosocial risks; named ESENER 1 and ESENER 2. Since micro-enterprises (employing 1–5 employees) were not included in ESENER 2 (EU-OSHA, 2015), an important part of the picture has been left unattended on a European level. This paper aims to address this gap by focussing on the case of Cyprus, since insufficient amount of micro enterprises from Cyprus participated in ESENER 2. A survey utilising ESENER-2 questions was adapted for exploring micro-enterprises' employees' perceptions and awareness about psychosocial risks and their management in the work setting. The main differences and some similarities that were spotted between the results of this study and ESENER-2 results regarding Cyprus are highlighted. The differences indicate that the size of the business and the peculiarities of the Cypriot context impact on the perception and management of psychosocial risks. Further research is required in the field of microenterprises that employ from 1 to 5 people, on an EU and international level with a special focus on psychosocial risk issues in micro-enterprises at the service sector and family businesses.